A degradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesion and a preparation method thereof

CN122954869APending Publication Date: 2026-10-23刘姿雨
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510462323.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种治疗宫腔粘连的可降解中药复合水凝胶及其制备方法,解决了因作用面窄、靶点不全导致疗效有限的问题

Benefits of technology

[0049]1、本发明通过采用特定比例组合的丹参、川芎、熟地黄、白芍、当归、败酱草、鸡血藤与泽兰中药配方,有机覆盖活血化瘀、补血养阴、清热解毒等多个治疗环节,达到了药效协同、作用针对性强的效果。相较于现有技术中仅采用单味或少量组方药材的治疗方案,解决了因作用面窄、靶点不全导致疗效有限的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122954869A_ABST
    Figure CN122954869A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of traditional Chinese medicine preparation, and discloses a degradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesion and a preparation method thereof, which comprises the following component ingredients: 10-30 parts of Danshen; 5-15 parts of Chuanxiong; 10-20 parts of Shudihuang; 5-15 parts of Baishao; 5-15 parts of Danggui; 3-8 parts of Baijiaocao; 5-10 parts of Jixueteng; and 3-8 parts of Zelan, wherein the hydrogel matrix is composed of the following ingredients: 1-3% of sodium alginate; 0.5-1% of chitosan; and 5-10% of PLGA (polylactic acid-glycolic acid copolymer). The traditional Chinese medicine formula of Danshen, Chuanxiong, Shudihuang, Baishao, Danggui, Baijiaocao, Jixueteng and Zelan in a specific proportion is used to organically cover blood-activating and stasis-removing, blood-supplementing and yin-nourishing, heat-clearing and toxin-resolving and other multiple treatment links, so that the effect of synergistic pharmacodynamics and strong targeting is achieved, and the problem of limited curative effect caused by narrow action surface and incomplete target is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of traditional Chinese medicine preparation technology, specifically to a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions and its preparation method. Background Technology

[0002] Intrauterine adhesions (IUA) refer to the formation of fibrous adhesions in the basal layer of the endometrium due to damage caused by factors such as trauma, infection, or postoperative complications. This can lead to serious consequences such as menstrual abnormalities, infertility, or recurrent miscarriages. With the increasing prevalence of intrauterine procedures, such as induced abortion and hysteroscopic surgery, the incidence of IUA has risen significantly, and the recurrence rate is high. Clinical treatment primarily involves adhesiolysis, supplemented by medication, intrauterine stents, and regenerative materials to prevent recurrence. However, the treatment effectiveness remains unstable, especially in preventing postoperative re-adhesion and promoting endometrial repair, which still presents many challenges.

[0003] While existing anti-adhesion materials such as hyaluronic acid, hydrogels, and intrauterine stents have made some progress in physical isolation, they are mostly based on single materials and lack adaptability to the complex pathological environment of the uterine cavity. Hydrogels prepared from traditional natural polymers such as chitosan or sodium alginate are structurally unstable in vivo, degrade too quickly, and are difficult to achieve sustained drug release.

[0004] Meanwhile, some drugs are directly mixed into hydrogels and released rapidly through osmosis in body fluids, leading to problems such as sudden changes in concentration, short-lived efficacy, and inactivation of active ingredients. Furthermore, commonly used traditional Chinese medicine treatments often employ local infusion or suppository forms, resulting in high dosing frequency, low absorption efficiency, and difficulty in achieving a treatment model that balances targeted and controlled therapy. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions and its preparation method, solving the problem of limited efficacy due to narrow action area and incomplete target.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions, comprising the following components:

[0007] 10-30 parts of Salvia miltiorrhiza;

[0008] 5-15 parts of Ligusticum chuanxiong;

[0009] 10-20 parts of prepared Rehmannia root;

[0010] 5-15 parts of white peony root;

[0011] 5-15 parts of Angelica sinensis;

[0012] Patrinia scabiosifolia 3-8 parts;

[0013] 5-10 parts of chicken blood vine;

[0014] 3-8 portions of Zeelandia diffusa.

[0015] Furthermore, the above-mentioned Chinese medicine ingredients are selected from traditional Chinese medicine materials related to the pathogenesis of "stasis, deficiency, and heat". Danshen and Chuanxiong are the principal herbs to promote blood circulation and remove blood stasis. Rehmannia glutinosa and Paeonia lactiflora are the assistant herbs to nourish blood and yin. Angelica sinensis nourishes blood and promotes blood circulation, together relieving the condition of blood deficiency and stasis. Patrinia scabiosaefolia clears heat and detoxifies, and treats inflammation. Spatholobus suberectus and Lycopus lucidus are the adjuvant herbs to enhance the effects of promoting blood circulation and regulating menstruation, and also have the effects of promoting diuresis and reducing swelling. The combined ingredients work synergistically to help improve the endometrial repair obstacles and inflammatory microenvironment in the formation mechanism of intrauterine adhesions.

[0016] Preferably, the hydrogel matrix is ​​composed of the following components:

[0017] Sodium alginate 1-3%;

[0018] Chitosan 0.5-1%;

[0019] PLGA (polylactic acid-glycolic acid copolymer) 5-10%;

[0020] Sodium alginate provides the basic structure of the gel, chitosan enhances the mechanical strength and adhesion of the hydrogel, and PLGA is used to regulate the degradation rate of the hydrogel.

[0021] Furthermore, sodium alginate can form a stable gel network, chitosan increases the mechanical properties and adhesion of the system through hydrogen bonding and electrostatic interactions, which is conducive to stable local residence in the uterine cavity, and PLGA is a controllable degradable material. Its ester bond hydrolysis rate determines the drug release rhythm. The combination of the three can take into account both support and controlled release performance, meeting the clinical needs for sustained local drug action.

[0022] Preferably, the microcapsule encapsulation material is prepared using the following method:

[0023] Compound Chinese herbal extracts are encapsulated in chitosan or gelatin matrix using emulsion polymerization or solvent evaporation methods.

[0024] Emulsion polymerization disperses traditional Chinese medicine extracts in an aqueous phase to form an emulsion, which is then mixed with an organic solvent to form microcapsules.

[0025] The solvent evaporation method obtains microcapsule particles by evaporating the solvent, with the particle size controlled between 100-500 μm.

[0026] Furthermore, microencapsulation technology can prevent premature release or degradation of active ingredients while maintaining the bioactivity of the drug. The natural polymeric properties of chitosan and gelatin provide good encapsulation and controlled-release structures, and particle size control helps optimize uniform distribution and release behavior in the hydrogel network.

[0027] Preferably, the hydrogel matrix is ​​supported and degradation controlled by a composite of sodium alginate, chitosan and PLGA. The hydrogel does not contain responsive materials, ensuring its stability and drug release regulation within the uterine cavity.

[0028] Furthermore, the absence of pH or temperature-responsive materials enhances structural stability and prevents structural damage caused by drastic environmental changes; the combination of the three basic materials provides mechanical support while achieving controlled-release efficacy, making it suitable for clinical scenarios where the intrauterine microenvironment is relatively constant but requires stable sustained release.

[0029] A method for preparing a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions includes the following steps:

[0030] Step 1: Prepare a compound Chinese medicine extract by mixing Danshen, Chuanxiong, Rehmannia glutinosa, Paeonia lactiflora, Angelica sinensis, Patrinia scabiosaefolia, Spatholobus suberectus and Lycopus lucidus in a certain proportion and extracting the effective components.

[0031] Step 2: Prepare sodium alginate solution, chitosan solution and PLGA solution separately, and mix them to form a composite hydrogel matrix solution;

[0032] Step 3: Add the Chinese herbal extract into the hydrogel matrix and perform microcapsule encapsulation using emulsion polymerization or solvent evaporation to obtain Chinese herbal composite microcapsules.

[0033] Step 4: React the microcapsule solution with a cross-linking agent to cross-link and form a three-dimensional herbal composite hydrogel.

[0034] Step 5: Freeze-dry the formed hydrogel to obtain traditional Chinese medicine composite hydrogel powder or freeze-dried product.

[0035] Step 6: Before or during application, an enzymatic hydrolysant can be added to regulate the degradation behavior of the hydrogel in vivo, thereby achieving sustained drug release.

[0036] Furthermore, the overall method adopts a closed-loop preparation process of "Chinese herbal medicine extraction - carrier construction - microcapsule embedding - cross-linking gelation - drying treatment". Each step ensures the preservation of active ingredients and the stable formation of controlled-release carriers, and regulates the release rhythm in vivo through enzymatic hydrolysis to adapt to the time window of uterine cavity repair.

[0037] Preferably, the extraction of traditional Chinese medicine in step 1 is carried out by water extraction or alcohol extraction, and the concentration of the extract is controlled at 1-5 g / mL to ensure the stable presence of the main active ingredients. Water extraction refers to adding the raw Chinese medicine to 10-20 times its mass of deionized water and heating it in a water bath at 60-90℃ for 1-3 hours. After filtering the residue and concentrating, the extract is obtained. Alcohol extraction refers to adding the raw Chinese medicine to 10-20 times its mass of 30-80% ethanol solution and soaking or refluxing it at room temperature to 60℃ for 1-3 hours. After filtering the residue and concentrating, the extract is obtained.

[0038] Furthermore, water extraction is suitable for extracting polysaccharides and water-soluble flavonoids, while alcohol extraction can extract fat-soluble active ingredients, such as volatile oils and phenolic acids. Combining or selectively using the two methods can obtain the main efficacy basis of compound Chinese medicines, and controlling the concentration of the extract can ensure the consistency of efficacy.

[0039] Preferably, in step 2, the solution concentrations of sodium alginate, chitosan, and PLGA are 1%-3%, 0.5%-1%, and 5%-10%, respectively, and the three are mixed in a mass ratio of 1:1:2 to 3:1:4.

[0040] Furthermore, controlling the material ratio helps to regulate the cross-linking density and microstructure morphology of the hydrogel, thereby affecting its swelling properties, mechanical strength, and degradation rate, meeting the requirements for the synchronization of support and biodegradation during the repair of intrauterine tissue.

[0041] Preferably, the particle size of the herbal microcapsules formed in step 3 is controlled between 100-500 μm, and the method used is emulsion polymerization or solvent evaporation, which is used to optimize drug encapsulation efficiency and release stability.

[0042] Furthermore, the appropriate particle size range ensures good dispersibility of microcapsules in the hydrogel network, while controlling the release channels of the encapsulated components, improving the consistency of controlled release, avoiding release mutations, and facilitating the maintenance of therapeutic efficacy.

[0043] Preferably, the crosslinking agent used in step 4 is glutaraldehyde or sodium sulfate, with a concentration controlled at 0.5%-2%. The crosslinking reaction is carried out at room temperature for 1-4 hours to form a stable three-dimensional hydrogel structure.

[0044] Furthermore, the crosslinking agent constructs a three-dimensional network structure by undergoing condensation or ionic crosslinking reactions with the matrix material, thereby improving gel strength and stability; concentration and time control can adjust the degree of crosslinking, thus affecting the size of the release pores and the degradation rhythm.

[0045] Preferably, the enzymatic hydrolysant added in step 6 is a protease or plasmin, the enzymatic hydrolysis temperature is 37°C, and the reaction time is 24-48 hours, which is used to regulate the degradation rate of the hydrogel and the drug release process.

[0046] Furthermore, proteases or plasmin can specifically degrade the natural polymer structure in the cross-linked network, causing the hydrogel to gradually disintegrate and promoting drug release; controlled enzymatic hydrolysis under body temperature conditions can achieve spatial and temporal degradation and targeted release.

[0047] This invention provides a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions and its preparation method.

[0048] It has the following beneficial effects:

[0049] 1. This invention utilizes a specific combination of traditional Chinese medicine ingredients, including Salvia miltiorrhiza, Ligusticum chuanxiong, Rehmannia glutinosa, Paeonia lactiflora, Angelica sinensis, Patrinia scabiosaefolia, Spatholobus suberectus, and Lycopus lucidus, to organically cover multiple therapeutic aspects such as promoting blood circulation and removing blood stasis, nourishing blood and yin, and clearing heat and detoxifying. This achieves synergistic effects and highly targeted efficacy. Compared to existing treatment plans that use only single herbs or small amounts of other ingredients, this invention solves the problem of limited efficacy due to a narrow scope of action and incomplete target targeting.

[0050] 2. This invention achieves a functional balance between mechanical strength, biodegradability, and biocompatibility by constructing a ternary composite hydrogel system composed of sodium alginate, chitosan, and PLGA, endowing the hydrogel with excellent physical formability and controlled drug release capability. Unlike traditional hydrogels that use a single natural polymer material, the defects of uncontrollable degradation rate and structural instability are effectively overcome.

[0051] 3. This invention introduces traditional Chinese medicine compound ingredients into a hydrogel carrier system via microencapsulation. Particle size and encapsulation performance are precisely controlled using emulsion polymerization or solvent evaporation methods, enabling the traditional Chinese medicine to achieve time-dependent release in vivo. Unlike existing methods that directly mix drug solutions into hydrogels, leading to abrupt changes in release rate, this design overcomes key technical obstacles such as uneven release and drug inactivation.

[0052] 4. This invention utilizes enzymatic hydrolysis to gradually degrade the hydrogel within the uterine cavity, simultaneously releasing the active ingredients. The release behavior is adjustable, and the duration of action is controllable. Compared to traditional release methods that rely on the natural hydrolysis of the material itself, this invention solves the practical problems of short release time and insufficient efficacy maintenance, improving the clinical suitability and operational flexibility of the formulation system in local uterine treatment. Attached Figure Description

[0053] Figure 1 This is a flowchart of the method of the present invention. Detailed Implementation

[0054] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0055] Please see the appendix Figure 1 :

[0056] Example 1: A compound traditional Chinese medicine hydrogel system constructed with balanced formulation

[0057] Take 20 parts of Salvia miltiorrhiza, 10 parts of Ligusticum chuanxiong, 15 parts of Rehmannia glutinosa, 10 parts of Paeonia lactiflora, 10 parts of Angelica sinensis, 5 parts of Patrinia scabiosaefolia, 7 parts of Spatholobus suberectus, and 5 parts of Lycopus lucidus. Mix them evenly, grind them into coarse powder, and pour them into an extraction vessel with a volume three times that of the vessel. Add 15 times the mass of deionized water, heat to 85℃, and extract in a water bath for 2 hours. The resulting extract is coarsely filtered, filtered through an 80-mesh screen, and concentrated under reduced pressure to a concentration of 3.5 g / mL.

[0058] Matrix preparation: A 2% sodium alginate aqueous solution, a 0.75% chitosan acetic acid solution, and an 8% PLGA chloroform solution were mixed in a mass ratio of 2:1:3. The stirring speed was set to 300 rpm for 25 minutes. Tween-80 was added as an emulsifier at a concentration of 0.2%. The concentrated herbal extract was added dropwise to the chitosan syrup to form W / O emulsion microcapsules with a particle size of 200 μm. These microcapsules were then incorporated into the gel matrix.

[0059] During the cross-linking stage, 1% glutaraldehyde solution was added dropwise at a mass-to-volume ratio of 1:10, and the reaction was carried out at room temperature for 2 hours. After static solidification, the membrane was frozen at -20°C for 12 hours and then freeze-dried under vacuum for 48 hours to obtain the final hydrogel membrane. The membrane has a regular overall structure, a light brown color, and uniform pores, making it suitable for postoperative intrauterine application.

[0060] Example 2: Construction of PLGA-dominated ethanol-extracted gel structure

[0061] Take 25 parts of Salvia miltiorrhiza, 8 parts of Ligusticum chuanxiong, 20 parts of Rehmannia glutinosa, 8 parts of Paeonia lactiflora, 12 parts of Angelica sinensis, 6 parts of Patrinia scabiosaefolia, 8 parts of Spatholobus suberectus, and 5 parts of Lycopus lucidus. Grind them into 60-mesh powder, add 14 times their weight of 30% ethanol, and reflux extract in a 60℃ water bath for 90 minutes. Filter, repeat the extraction once, combine the liquids and concentrate under reduced pressure to 4.0 g / mL.

[0062] Materials used: 1% sodium alginate, 0.5% chitosan, and 10% PLGA, mixed in a mass ratio of 1:1:4. The herbal extract was added to the PLGA phase at a volume ratio of 1:3, followed by dropwise addition of liquid paraffin. The solvent was evaporated by low-speed stirring to obtain microcapsule structures. The particle size distribution was relatively large, concentrated around 400 μm.

[0063] The obtained microcapsule powder was uniformly mixed into the gel mixture, followed by the introduction of a 0.5% sodium sulfate solution for ionic cross-linking. The stirring time was controlled to be within 3 hours to avoid structural damage. The resulting hydrogel was a flexible, semi-solid state. After vacuum freeze-drying, it was cut into regular sheet-like products. These can be directly implanted into the uterine cavity, are not prone to displacement, have a long degradation period, and exhibit stable drug release.

[0064] Example 3: Construction and Degradation Regulation of Particle Size Controlled Microcapsules

[0065] The formula consists of 15 parts Salvia miltiorrhiza, 6 parts Ligusticum chuanxiong, 10 parts Rehmannia glutinosa, 8 parts Paeonia lactiflora, 7 parts Angelica sinensis, 4 parts Patrinia scabiosaefolia, 5 parts Spatholobus suberectus, and 3 parts Lycopus lucidus. Water extraction was performed using 14 times its weight of deionized water, and the extraction was carried out at 85℃ for 1.5 hours. After filtering, the residue was concentrated under reduced pressure to 2.5 g / mL, resulting in a dark brown liquid, which was then stored for later use.

[0066] Sodium alginate 2.5%, chitosan 1%, and PLGA 5%. The three solutions were prepared separately in a mass ratio of 3:1:2. The herbal extract was encapsulated using emulsion polymerization, followed by ultrasonic emulsification to prepare microcapsules at a controlled frequency of 20 kHz for 8 minutes. This resulted in herbal microcapsules with an average particle size of 150 μm.

[0067] The prepared microcapsules were added to a premixed gel solution, and then a 1.2% glutaraldehyde solution was slowly added dropwise. The reaction temperature was set at 25°C, and the reaction time was 1.5 hours. Immediately after gel formation, the gel was transferred to a mold and pre-frozen at -30°C for 6 hours, followed by freeze-drying for 48 hours. The resulting gel had a regular structure with continuous pores visible in the cross-section, suitable for applications requiring gradual degradation and release.

[0068] Example 4: Structural Adaptation Construction Scheme under Variation of Crosslinking Agent

[0069] The selected medicinal materials included 30 parts of Salvia miltiorrhiza, 12 parts of Ligusticum chuanxiong, 18 parts of Rehmannia glutinosa, 12 parts of Paeonia lactiflora, 10 parts of Angelica sinensis, 5 parts of Patrinia scabiosaefolia, 10 parts of Spatholobus suberectus, and 8 parts of Lycopus lucidus. After pulverizing, 18 times the volume of 80% ethanol was added, and the mixture was pre-soaked at room temperature for 1 hour, followed by reflux extraction at 60℃ for 90 minutes. The two extractions were combined and concentrated, with the final concentration controlled at 3.8 g / mL.

[0070] The basic hydrogel components are sodium alginate 1.5%, chitosan 0.5%, and PLGA 7%. They are mixed in a mass ratio of 2:1:4 to form the gel matrix. Gelatin is used instead of chitosan for the microcapsules. A concentrated traditional Chinese medicine solution is mixed with a 10% gelatin solution, and microspheres of approximately 250 μm are generated using a solvent evaporation method.

[0071] Ion crosslinking was performed using a 0.5% sodium sulfate aqueous solution, with the crosslinking process set to a static reaction state for 3 hours. Post-processing included mold shaping, freezing at -20℃ for 12 hours, and vacuum freeze-drying for 36 hours. The dried gel product was cut into circular tablets for in-situ application after clinical uterine cavity surgery. Release curve tests under different pH conditions showed that it has stable responsiveness and adapts to varying physiological environments.

[0072] Comparative Example 1: Single Herb System without Compound Formula

[0073] This comparative example corresponds to Example 1.

[0074] Raw materials: 20 portions of single-herb Salvia miltiorrhiza were selected; no compound herbal combinations or other Chinese herbal ingredients were added. The herb was pulverized into coarse powder, added with 15 times the amount of deionized water, and heated in a water bath at 85℃ for 2 hours. After filtration, the powder was concentrated to 3.5 g / mL.

[0075] Matrix preparation: Use the same aqueous solutions of sodium alginate, chitosan, and PLGA in a ratio of 2:1:3, and stir evenly to form a matrix.

[0076] Microcapsule preparation: The emulsion method was used for encapsulation. The extract was directly added to the mixed matrix without microencapsulation, and the resulting hydrogel was directly solidified.

[0077] Crosslinking step: Add 1% glutaraldehyde, react for 2 hours, and finally freeze dry.

[0078] Difference: This comparative example only used Danshen alone, lacking the synergistic effect of other herbs, and did not perform microencapsulation, resulting in a relatively rapid drug release and the inability to achieve gradual control.

[0079] Comparative Example 2: Basic Controlled-Release System without PLGA

[0080] This comparative example corresponds to Example 2.

[0081] Raw materials: The medicinal materials used were exactly the same as in Example 2, using the same concentration (4.0 g / mL) of alcohol extract.

[0082] Matrix preparation: A solution of 1% sodium alginate and 0.5% chitosan was prepared in a 2:1 ratio. PLGA was omitted in this step, and only sodium alginate and chitosan were used.

[0083] Microcapsule preparation: Using the same solvent evaporation method, the traditional Chinese medicine liquid and PLGA were encapsulated together, but the PLGA was removed here to obtain PLGA-free microcapsules.

[0084] Crosslinking step: Ionic crosslinking is performed using a 0.5% sodium sulfate solution for 3 hours.

[0085] Difference: The comparative example after removing PLGA lost its main controlled-release material, resulting in a faster gel release rate and a less stable structure than Example 2, thus failing to achieve the desired sustained drug release effect.

[0086] Comparative Example 3: Conventional gel systems without controlling microcapsule size

[0087] This comparative example corresponds to Example 3.

[0088] Raw materials: The same proportion of medicinal materials as in Example 3 were used, and the extraction concentration was 2.5 g / mL.

[0089] Matrix preparation: Sodium alginate, chitosan, and PLGA were mixed in a ratio of 3:1:2 without particle size control. Microcapsules were formed directly through a stirring emulsification method; particle size was not rigorously screened, potentially resulting in significant variations and inadequate control of the average particle size.

[0090] Microcapsule preparation: If the particle size of the microcapsules is not controlled, the particle size distribution may be too wide, and some microcapsules may be too large or too small, which will affect the stability of the hydrogel.

[0091] Crosslinking step: Add 1% glutaraldehyde, react at room temperature for 2 hours, and freeze dry.

[0092] Difference: This comparative ratio did not perform particle size screening, resulting in uneven microcapsule particle size, which affects the uniform release rate of the drug and cannot guarantee the stability and sustainability of the drug efficacy.

[0093] Comparative Example 4: Crosslinking agent used alone, without ionic crosslinking

[0094] This comparative example corresponds to Example 4.

[0095] Raw materials: The medicinal materials used were the same as in Example 4, and the concentration of the extract was 3.8 g / mL.

[0096] Matrix preparation: Sodium alginate 1.5%, chitosan 0.5%, PLGA 7% in a ratio of 2:1:4, forming the basic gel material.

[0097] Microcapsule preparation: The same microcapsule encapsulation method as in Example 4 was used. After the drug solution was mixed with gelatin, microcapsules were formed by solvent evaporation, and the particle size was controlled at 250 μm.

[0098] Crosslinking step: Unlike Example 4, this comparative example uses only glutaraldehyde as a crosslinking agent and does not use sodium sulfate for ionic crosslinking. The reaction temperature is set to room temperature, and the crosslinking time is 3 hours.

[0099] Difference: The comparative example without sodium sulfate ion crosslinking agent resulted in a simpler crosslinking reaction, poor structural stability and drug release control, and could not achieve the best effect expected in Example 4. The drug may be released more rapidly.

[0100] Experiment 1: Comparison of Microencapsulation and Drug Release Rate

[0101] Experimental Objective: The purpose of this experiment is to compare the differences in drug release rates between Example 1 and Comparative Example 1, focusing on the effect of microencapsulation on drug release control characteristics. Drug release tests using hydrogels in a simulated physiological environment will verify the advantages of microencapsulation in delaying drug release and enhancing drug release control.

[0102] Experimental steps:

[0103] Sample preparation:

[0104] Example 1: Prepare hydrogel sheets containing microcapsules according to the formula. The thickness is 2 mm and the size is 2 cm x 2 cm to ensure uniformity.

[0105] Comparative Example 1: Prepared microcapsule-free hydrogel sheets with the same thickness and size as in the Example.

[0106] Drug release test:

[0107] The hydrogel samples were each immersed in 50 mL of PBS solution with a pH of 7.4 and a temperature of 37 °C.

[0108] Every hour, 5 mL of sample was taken, and the released Chinese herbal components (such as tanshinone and flavonoids) at each time point were analyzed using high performance liquid chromatography (HPLC).

[0109] Data collection and analysis:

[0110] Record the drug concentration data released at each time point and calculate the cumulative amount of drug released.

[0111] Each experimental group was sampled 12 times, with sampling points including 1 hour, 4 hours, 12 hours, 24 hours, 48 ​​hours, and 72 hours.

[0112] Data processing and comparison:

[0113] Plot drug release curves to compare the drug release rates of Example 1 and Comparative Example 1 at different time points.

[0114] Calculate the drug release half-life for each group of samples and analyze the differences in release rates.

[0115] Experimental setup:

[0116] Temperature: 37℃ (simulating physiological body temperature)

[0117] Solution: PBS (pH 7.4)

[0118] Soaking volume: 50mL

[0119] Drug release analysis: High-performance liquid chromatography (HPLC)

[0120] Number of experiments per group: 3 independent experiments

[0121] Table Title: Comparison of Drug Release Rates between Example 1 and Comparative Example 1

[0122] 1 0.45 0.88 4 1.03 1.75 12 2.12 3.41 24 3.01 4.50 48 3.58 5.78 72 4.10 6.20

[0123] Summarize

[0124] Example 1, featuring microencapsulation, demonstrates a relatively smooth and sustained drug release profile. This release profile is closely related to the structural characteristics of the microcapsule encapsulation. The presence of the microcapsule provides an effective barrier, slowing drug leakage and controlling the release rate in the body. By encapsulating the drug component within a microcapsule, the drug is gradually released slowly through the microcapsule shell, preventing rapid drug loss. This controlled release method not only prolongs the duration of efficacy but also avoids fluctuations in blood drug concentration peaks and troughs, reducing drug side effects. In contrast, Example 1, which did not employ microencapsulation, exhibited a more rapid increase in drug release, potentially leading to a faster loss of efficacy and difficulty in maintaining a sustained therapeutic effect.

[0125] Microencapsulation not only plays a crucial role in drug stability but also effectively controls the rate of drug degradation. In Example 1, the microcapsules, through precise control of their particle size and the properties of the polymer material, enable more controllable drug release. On the other hand, in Comparative Example 1, which did not use microcapsules, the drug release rate was relatively rapid, with the release amount reaching a peak within a short period. This indicates that the use of microcapsules can significantly extend the drug's half-life and achieve sustained release.

[0126] Furthermore, the degree of cross-linking in the microencapsulated material plays a crucial role. Cross-linking enhances the stability of the hydrogel, thereby further improving the controllability of drug release. Through cross-linking, drug diffusion is restricted, further reducing large-scale release in the short term and ensuring that the drug's effect remains stable and sustained over a longer period. This phenomenon is consistent with the controlled degradation mechanism and controlled release method proposed in this invention, demonstrating the enormous potential of microencapsulation in drug delivery.

[0127] Experiment 2: Effect of PLGA on controlled release

[0128] Experimental Objective: This experiment aims to compare the effect of PLGA introduction on the controlled-release effect of hydrogels in Example 2 and Comparative Example 2. Drug release tests will be conducted to verify the role of PLGA as a controlled-release material in delaying drug release and enhancing its controlled-release properties.

[0129] Experimental steps:

[0130] Sample preparation:

[0131] Example 2: Prepare PLGA-containing hydrogel sheets according to the predetermined formula, with a size of 2cm x 2cm and a thickness of 2mm, to ensure material uniformity.

[0132] Comparative Example 2: Hydrogels were prepared using the same method, but PLGA was removed, and only sodium alginate and chitosan were used to form hydrogels.

[0133] Drug release test:

[0134] Each group of hydrogel samples (10 pieces) was immersed in 50 mL of PBS solution at pH 7.4 and temperature 37 °C to simulate the in vivo environment.

[0135] Every hour, 5 mL of sample was taken and the concentration of the drug in the solution was analyzed using UV-Vis spectroscopy.

[0136] Record the cumulative release of the drug and take samples periodically (1 hour, 4 hours, 12 hours, 24 hours, 48 ​​hours, 72 hours).

[0137] Data collection and analysis:

[0138] After sampling and analysis at each time point, drug release curves were plotted to compare the differences in drug release rates between Example 2 and Comparative Example 2.

[0139] The drug release half-life and average release rate of the two groups were calculated, and the effect of PLGA on the drug release rate was further analyzed.

[0140] Experimental setup:

[0141] Temperature: 37℃ (simulating physiological body temperature)

[0142] Solution: PBS (pH 7.4)

[0143] Soaking volume: 50mL

[0144] Drug release analysis: UV-Vis spectroscopy, sampling every 1 hour.

[0145] Table Title: Comparison of Drug Release Rates between Example 2 and Comparative Example 2

[0146] 1 0.28 0.78 4 0.89 1.56 12 1.65 3.02 24 2.27 4.25 48 2.85 5.63 72 3.20 6.10

[0147] Summarize

[0148] The introduction of PLGA significantly altered the drug release characteristics of the hydrogel. In Example 2, the addition of PLGA played a crucial role in the structure of the hydrogel. As a biodegradable polymer, it slowed down the degradation rate of the hydrogel, thereby enabling gradual drug release. The presence of PLGA increased the hydrophilicity and biocompatibility of the hydrogel, resulting in a more stable drug release and avoiding the rapid release phenomenon that was more pronounced in the control group. Compared to Comparative Example 2, the hydrogel without PLGA had a faster release rate, indicating that PLGA not only played a role in sustained drug release but also affected the structural stability of the hydrogel.

[0149] Furthermore, the degradation properties of PLGA allow the hydrogel to more effectively control drug release time. In Example 2, drug release is a relatively long process; this delayed release allows the drug concentration in the body to remain within a stable range, avoiding potentially drastic fluctuations in blood drug concentration and reducing the risk of side effects. As a controlled-release material, PLGA can effectively prolong the duration of drug action, providing a more stable therapeutic effect.

[0150] From the perspective of degradation mechanism, the controlled release structure formed by PLGA in the hydrogel is closely related to its tunable degradation rate and physical properties. Its degradation in the aqueous environment is achieved through hydrolysis; over time, the PLGA segments gradually break down, allowing for the slow release of the encapsulated drug. In contrast, Comparative Example 2 lacks the support of PLGA, resulting in rapid drug release and structural instability. This leads to a much higher drug release rate than Example 2, a lack of long-lasting effect, and a more limited therapeutic efficacy.

[0151] Experiment 3: Effect of cross-linking agent on hydrogel degradation rate

[0152] Experimental Objective: This experiment aims to investigate the effects of cross-linking agents (glutaraldehyde and sodium sulfate) on the degradation rate of hydrogels. By comparing the degradation rates of hydrogels treated with different cross-linking agents, the role of cross-linking agents in controlling hydrogel degradation and drug release rates is verified.

[0153] Experimental steps:

[0154] Sample preparation:

[0155] Example 3: Prepare a hydrogel sheet containing sodium sulfate crosslinking according to the formula. The sheet has a size of 2cm x 2cm and a thickness of 2mm.

[0156] Comparative Example 3: Hydrogels were prepared using the same method, and crosslinked with 1% glutaraldehyde to maintain consistent sample thickness and size.

[0157] Degradation experiment:

[0158] Each group of hydrogels (10 pieces in total) was immersed in 50 mL of PBS solution at pH 7.4 and temperature 37 °C to simulate a physiological environment.

[0159] Every other day, the hydrogel sample was taken out, weighed, and the mass loss of the hydrogel was recorded.

[0160] Samples were taken every 3 days to observe the morphological changes of the hydrogel and record its degradation process.

[0161] Data collection and analysis:

[0162] Calculate the change in hydrogel mass at each time point and plot the curve of hydrogel mass loss over time.

[0163] The change in the degree of crosslinking of the hydrogel during the degradation process was analyzed using FTIR (Fourier Transform Infrared Spectroscopy) to further evaluate the effect of the crosslinking agent on the structural stability of the hydrogel.

[0164] Data processing:

[0165] Calculate the degradation half-life of the hydrogel and analyze the effect of the crosslinking agent on the degradation rate.

[0166] Compare the differences in mass loss between Example 3 and Comparative Example 3 within the same time period.

[0167] Experimental setup:

[0168] Temperature: 37℃

[0169] Solution: PBS (pH 7.4)

[0170] Soaking volume: 50mL

[0171] Degradation analysis: gravimetric method, FTIR analysis

[0172] Table Title: Comparison of Degradation Rates between Example 3 and Comparative Example 3

[0173]

[0174]

[0175] Summarize

[0176] The role of cross-linking agents in the hydrogel degradation process is evident. In Example 3, the sodium sulfate cross-linking significantly slowed the hydrogel degradation rate, ensuring gradual drug release. As an ionic cross-linking agent, sodium sulfate enhances the network structure stability of the hydrogel by interacting with the negative charges in sodium alginate and chitosan molecules. This makes the degradation process of the hydrogel in vivo much slower, effectively prolonging the drug release time. In contrast, the glutaraldehyde cross-linking in Comparative Example 3 failed to effectively delay the degradation process, resulting in faster hydrogel mass loss, a significantly increased release rate, and a potential rapid release of the drug within a short period, lacking sustainability.

[0177] From a mechanistic perspective, sodium sulfate, through its cross-linked structure formed by ionic bonds, makes the network within the hydrogel more compact and stable, slowing down the entry of water molecules and the initiation of degradation reactions. Glutaraldehyde, on the other hand, cross-links molecular chains through covalent bonds, forming a simpler network structure. This lack of effective control over the hydrogel structure leads to a faster degradation rate. In this situation, drug release also exhibits more dramatic peak changes, and this rapid release is not conducive to long-term treatment.

[0178] The choice of crosslinking agent directly affects the degradation mechanism of the hydrogel and the drug release pattern. The crosslinking strategy in Example 3, using sodium sulfate, enhances the stability of the hydrogel, enabling continuous and stable drug release without significant loss in a short period. In contrast, the glutaraldehyde crosslinking used in Comparative Example 3 leads to excessively rapid degradation and drug release, failing to meet the requirements for long-acting controlled release. This again demonstrates the crucial role of crosslinking agents in controlling drug release and maintaining the structural stability of the hydrogel.

[0179] Experiment 4: Effect of microcapsule particle size on the stability of hydrogel structure

[0180] Experimental Objective: This experiment aims to investigate the effect of microcapsule size on the structural stability of hydrogels and to verify the influence of particle size control on hydrogel degradation and stability properties. The effects of size-controlled and uncontrolled microcapsules on hydrogel stability and drug release will be compared.

[0181] Experimental steps:

[0182] Sample preparation:

[0183] Example 4: Prepare hydrogel sheets containing microcapsules according to the formula. The microcapsule particle size is controlled at about 250 μm, the size is 2cm x 2cm, and the thickness is 2mm.

[0184] Comparative Example 4: Hydrogels were prepared using the same method, but the microcapsule particle size was not controlled. The particle size range was large, ranging from 100 μm to 500 μm, while the size and thickness remained consistent.

[0185] Drug release and structural stability experiments:

[0186] Each group of hydrogel samples (10 pieces in total) was immersed in 50 mL of PBS solution at pH 7.4 and temperature 37 °C to simulate a physiological environment.

[0187] Take a 5 mL sample every hour and analyze the drug concentration in the solution using high performance liquid chromatography (HPLC).

[0188] Observe the appearance changes of the hydrogel every 3 days and record the damage to the hydrogel.

[0189] Degradation and structural stability analysis:

[0190] The hydrogel samples were weighed every 3 days, and the changes in the mass of the hydrogel were recorded.

[0191] The surface morphology of the samples was observed using scanning electron microscopy (SEM) to evaluate the distribution and stability of microcapsules in the hydrogel.

[0192] Data collection and analysis:

[0193] Calculate the mass loss of the hydrogel at each time point and plot the curve of mass loss over time.

[0194] Plot drug release curves and compare the release differences between hydrogels with and without particle size control.

[0195] The morphological changes of hydrogels and the distribution of microcapsules in simulated body fluids were analyzed.

[0196] Experimental setup:

[0197] Temperature: 37℃

[0198] Solution: PBS (pH 7.4)

[0199] Soaking volume: 50mL

[0200] Drug release analysis: HPLC

[0201] Morphological observation: SEM, sampling and analysis every 3 days.

[0202] Table Title: Comparison of Drug Release and Stability in Controlled and Uncontrolled Hydrogels

[0203] 1 0.56 0.88 4 1.32 2.17 12 2.58 3.91 24 3.02 4.82 48 3.74 5.65 72 4.01 6.05

[0204] Summarize

[0205] By controlling the microcapsule particle size, Example 4 demonstrated a more stable drug release profile. Microcapsules with a relatively uniform particle size (around 250 μm) could form a more stable structure within the hydrogel, slowing down the rapid release of the drug. This structural stability was reflected in the mass loss of the hydrogel and the drug release rate. In contrast, the microcapsule particle size in Comparative Example 4 was unstable, with some microcapsules being too large or too small, leading to structural instability in the hydrogel during degradation and a more intense, less sustained drug release.

[0206] From a mechanistic perspective, the particle size control of microcapsules directly affects the pore structure of the hydrogel and the drug diffusion pathway. In Example 4, the microcapsules, due to their uniform particle size, formed a relatively uniform network structure, effectively controlling the drug release pathway. Water molecules slowly penetrated, the microcapsules gradually degraded, and the drug release was more stable. In contrast, in Comparative Example 4, the uneven particle size led to uneven distribution of microcapsules, with some microcapsules prone to rapid degradation, resulting in a sharp increase in the drug release rate and a lack of sustained release characteristics.

[0207] Controlling the microcapsule particle size not only affects drug release but also directly impacts the stability of the hydrogel. More uniform particle size control leads to a more even distribution of microcapsules within the hydrogel, thereby enhancing its structural stability. In contrast, in Comparative Example 4, where the particle size is non-uniform, microcapsules may concentrate in certain areas, causing rapid degradation of local structures and affecting overall stability. By adjusting the microcapsule particle size, the degradation rate and drug release characteristics of the hydrogel can be controlled to some extent, ensuring the durability and stability of the therapeutic effect.

[0208] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions, characterized in that, It includes the following components: 10-30 parts of Salvia miltiorrhiza; 5-15 parts of Ligusticum chuanxiong; 10-20 parts of prepared Rehmannia root; 5-15 parts of white peony root; 5-15 parts of Angelica sinensis; Patrinia scabiosifolia 3-8 parts; 5-10 parts of chicken blood vine; 3-8 portions of Zeelandia diffusa.

2. The biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions according to claim 1, characterized in that, The hydrogel matrix is ​​composed of the following components: Sodium alginate 1-3%; Chitosan 0.5-1%; PLGA (polylactic acid-glycolic acid copolymer) 5-10%; Sodium alginate provides the basic structure of the gel, chitosan enhances the mechanical strength and adhesion of the hydrogel, and PLGA is used to regulate the degradation rate of the hydrogel.

3. The biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions according to claim 1, characterized in that, The microcapsule-encapsulated material was prepared using the following method: Compound Chinese herbal extracts are encapsulated in chitosan or gelatin matrix using emulsion polymerization or solvent evaporation methods. Emulsion polymerization disperses traditional Chinese medicine extracts in an aqueous phase to form an emulsion, which is then mixed with an organic solvent to form microcapsules. The solvent evaporation method obtains microcapsule particles by evaporating the solvent, with the particle size controlled between 100-500 μm.

4. The biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions according to claim 1, characterized in that, The hydrogel matrix is ​​supported and degradation controlled by a composite of sodium alginate, chitosan and PLGA. The hydrogel does not contain responsive materials, ensuring its stability and drug release regulation within the uterine cavity.

5. A method for preparing a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions, applied to the biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions as described in claims 1-4, characterized in that, Includes the following steps: Step 1: Prepare a compound Chinese medicine extract by mixing Danshen, Chuanxiong, Rehmannia glutinosa, Paeonia lactiflora, Angelica sinensis, Patrinia scabiosaefolia, Spatholobus suberectus and Lycopus lucidus in a certain proportion and extracting the effective components. Step 2: Prepare sodium alginate solution, chitosan solution and PLGA solution separately, and mix them to form a composite hydrogel matrix solution; Step 3: Add the Chinese herbal extract into the hydrogel matrix and perform microcapsule encapsulation using emulsion polymerization or solvent evaporation to obtain Chinese herbal composite microcapsules. Step 4: React the microcapsule solution with a cross-linking agent to cross-link and form a three-dimensional herbal composite hydrogel. Step 5: Freeze-dry the formed hydrogel to obtain traditional Chinese medicine composite hydrogel powder or freeze-dried product. Step 6: Before or during application, an enzymatic hydrolysant can be added to regulate the degradation behavior of the hydrogel in vivo, thereby achieving sustained drug release.

6. The method for preparing a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions according to claim 5, characterized in that, In step 1, the extraction of traditional Chinese medicine is carried out using either water extraction or alcohol extraction. The concentration of the extract is controlled at 1-5 g / mL to ensure the stable presence of the main active ingredients. Water extraction involves adding the raw Chinese medicine to 10-20 times its weight of deionized water and heating it in a water bath at 60-90℃ for 1-3 hours. After filtering and concentrating, the extract is obtained. Alcohol extraction involves adding the raw Chinese medicine to 10-20 times its weight of a 30-80% ethanol solution and soaking or refluxing it at room temperature to 60℃ for 1-3 hours. After filtering and concentrating, the extract is obtained.

7. The method for preparing a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions according to claim 5, characterized in that, In step 2, the solution concentrations of sodium alginate, chitosan, and PLGA are 1%-3%, 0.5%-1%, and 5%-10%, respectively, and the three are mixed in a mass ratio of 1:1:2 to 3:1:

4.

8. The method for preparing a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions according to claim 5, characterized in that, The particle size of the traditional Chinese medicine microcapsules formed in step 3 is controlled between 100-500 μm. The method used is emulsion polymerization or solvent evaporation to optimize drug encapsulation efficiency and release stability.

9. The method for preparing a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions according to claim 5, characterized in that, The crosslinking agent used in step 4 is glutaraldehyde or sodium sulfate, with a concentration controlled at 0.5%-2%. The crosslinking reaction is carried out at room temperature for 1-4 hours to form a stable three-dimensional hydrogel structure.

10. The method for preparing a biodegradable traditional Chinese medicine composite hydrogel for treating intrauterine adhesions according to claim 5, characterized in that, The enzymatic hydrolysant added in step 6 is a protease or plasmin, the hydrolysis temperature is 37℃, and the reaction time is 24-48 hours, which is used to regulate the degradation rate of the hydrogel and the drug release process.